Universal screening detects two-times more thyroid disorders in early pregnancy than targeted high-risk case finding - Horacek, Jiri; Spitalnikova, Sylvie; Dlabalova, Blanka; Malirova, Eva; Vizda, Jaroslav; Svilias, Ioannis; Cepkova, Jitka; Mc Grath, Catherine; Maly, Jaroslav (European journal of endocrinology, 2010)
OBJECTIVE: Screening of thyroid disorders in pregnancy has been controversial. Recent recommendations favour targeted high-risk case finding, though this approach may miss a significant number of those affected. We aimed to assess the prevalence of accepted high-risk criteria in women with autoimmune thyroiditis and/or hypothyroidism detected from universal screening in an iodine-sufficient population. DESIGN: In 400 non-selected women in the 9-11th gestational week, thyroid-related tests were performed, and those with abnormalities were offered consultation. METHODS: TSH was determined by IRMA, and the upper cut-off value for screening was set at 3.5 mIU/l. For free thyroxine (FT(4)) and thyroperoxidase antibodies (TPO-Ab), RIAs were used, with cut-offs of <10 pmol/l and >50 IU/ml respectively. Endocrinological consultation included Doppler ultrasonography and was aimed to confirm autoimmune thyroiditis and/or hypothyroidism. The prevalence of consensus high-risk criteria was assessed. RESULTS: Among the 400 women, 65 (16.3%) had ≥1 abnormality: higher TSH was found in 10.3%, lower FT(4) in 2% and positive TPO-Ab in 8.3%. Fifty-one women were examined and followed up. Levo-T(4) treatment was initiated in 49 women for autoimmune thyroiditis (in 42), hypothyroidism (in 34) or both (in 27). Only 22 (45%) of 49 treated women fulfilled ≥1 high-risk criterion: most commonly family history (31%), history of miscarriage or preterm delivery (14%) and personal history (8%). CONCLUSIONS: Over half (55%) of pregnant women with abnormalities suggestive of autoimmune thyroiditis and/or hypothyroidism would be missed if only those with high-risk criteria were examined. A more extensive screening of thyroid autoimmunity and dysfunction seems warranted.
Keywords: gestační stáří; nemoci štítné žlázy; Female; Thyrotropin; autoprotilátky; Gestational Age; ženské pohlaví; lidé; těhotenství; Radioimmunoassay; autoimunitní tyreoiditida; Thyroiditis, Autoimmune; Hypothyroidism; Thyroxine; Thyroid Diseases; thyreotropin; Autoantibodies; komplikace těhotenství; thyroxin; Pregnancy Complications; Pregnancy; radioimunoanalýza; hypotyreóza; Humans